Biodegradable poly(butylene succinate-co-terephthalate) nanofibrous membranes functionalized with cyclodextrin polymer for effective methylene blue adsorption. Issue 110 (14th November 2016) - Wei, Zhenzhen; Liu, Yinli; Hu, Hongmei; Yu, Jianyong; Li, Faxue
Abstract : PBST and PBST/CDP nanofibrous membranes were prepared for the first time. PBST/CDP membranes were fabricated by means of in situ polymerization. The morphologies of membranes were dependent on the CDP content. PBST/CDP membranes exhibited excellent adsorption capacity. Abstract : The burgeoning electrospinning technology brings about a diversity of nanofibers and promotes their applications in various fields including wastewater treatment. Herein, we fabricated biodegradable poly(butylene succinate- co -terephthalate) (PBST) nanofibrous membranes by electrospinning for the first time and functionalized them with β-cyclodextrin polymer (CDP) through the in situ polymerization of CDP on the surface of PBST nanofibrous membranes. Furthermore, there was much higher efficiency in removing methylene blue (MB) dye on the resultant PBST/CDP nanofibrous membranes than that on pure CDP, or PBST nanofibrous membrane. The adsorption performance of the composite membranes to MB molecules was influenced greatly by the amount of CDP that dominated the surface area and surface morphologies of the prepared membranes. The adsorption kinetics of PBST/CDP nanofibrous membrane fitted well with the pseudo-second order model and Langmuir isotherm model well described the relationship between the adsorption capacity and initial MB solution concentration, exhibiting the maximum adsorption capacity of 90.9 mg g −1, which was much higher than the adsorption capacity of the other adsorbents. Considering the excellent adsorption performance of the as-prepared material, the PBST/CDP nanofibrous membranes is a promising candidate in environmental purification applications.